Penggunaan Teknologi Informasi, Keterampilan dan Pengetahuan, Serta Sumber Daya Keuangan Terhadap Praktik Manajemen Persediaan - Ahmatang Ahmatang; Muhammad Said (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
An optimal inventory management practice is graetly needed in retail business sector because of their highly varied inventories an uncertain demand for costumers needs. With an optimal inventory management practice, identification of the number of goods and costs needed would be acurate, This research aimed to test whether factors like use oh information technology, skills and knowladge, and financial resouces might influence the inventory management practice of germent retail business in Tarakan. The research data were obtained throughquestionnaire using Likert scalemethod with 27 questions, that the questionnaire was distributed to 85 garment retail business in Tarakan using a purposive sampling method. The data collected were analyzed descriptifvely using quantitative approach with computer program SPSS. The results of this research showed that the variables use of information technology, skilss and knowladge, and financial resource positifvely, significantly influenced inventory management practice. The reserach findings could be used for recommendation and evaluation in inventory management practice to accelerate business’s operational activities and satisfy customers’ demand.